Study of association of age and BMI with knee osteoarthritis among females in age group of 40 to 60 years in urban population of Kadapa town - Tondare, Devidas; Kumbhar, Suresh; Kishore, K. J.; Khadervali, N. (International Journal Of Community Medicine And Public Health, 2017)
Background: Knee osteoarthritis is a significant problem in ageing population as females are more prone for the disease compare to males. Increase in life expectancy has made ageing worldwide phenomenon including developing countries. Risk factors related to the knee osteoarthritis may be multiple but female sex, age and obesity are more common in any region of country and world. The aim and objective of the study was to estimate the prevalence of knee osteoarthritis among females in age group of 40 to 60 years and see the effect of age and weight of patient on knee osteoarthritis. Methods: Cross sectional study was conducted at field practice area of Community Medicine Department in Kadapa town among females in age group of 40 to 60 years. Total 150 females participated in the study from the urban health training centre area in one month (November-December 2011) and study was conducted with personal interviews of participants in preformed questionnaire after obtaining the consent. Results: 150 participants were enrolled in the study, in age group of 40 to 50 years 76 (50.67%) and 50 to 60 years 74 (49.33%). Total 63 (42%) participants were affected with knee osteoarthritis. Among them 25 (32.89%) participants were in the age group of 40-50 years and 38 (51.35%) in the age group of 50 to 60 years which is significantly more. As per BMI participant with BMI >25 were significantly more affected 29 (63.04%) compared with participants with normal BMI, 17 (33.33%). Conclusions: Knee osteoarthritis is significantly associated with advanced age and obesity.